Neural network in medical prognosis - Wan Ishak, Wan Hussain; Siraj, Fadzilah; Othman, Abu Talib (2001)
Artificial Neural Networks or in short, Neural networks (ANNs or NNs) is a computational paradigm that comprises mathematical, statistical, biological sciences and philosophy. These paradigms formulate a formula to form a brain like function, called artificial neuron. ANN is a powerful tool to enhance current medical diagnostic techniques. Several studies have proven that neural network out performed experience medical practitioners in various fields such as cardiology. Therefore, it is vital to explore the potentials of neural network to enhance and facilitates current medical practice.This paper reviewed the applications of NN in various medical applications. A model for Web-based Medical Diagnosis and Prediction is also presented.